PENERAPAN BIOETIKA KULTUR JARINGAN KENTANG GRANOLA L. TERHADAP PENGGUNAAN ZPT SINTETIS DI LABORATORIUM INSTANSI PERTANIAN SWASTA MEDAN - Galih Hikmal Romadhon; Maura Maharani; Putri Andini (Jurnal Agro Indragiri, 2026)
Abstract Tissue culture is a technique in which sterile plants, tissues, or plant organs propagate plants involved in the production of new individuals. The success of potato tissue culture is influenced by various factors, including the culture medium, growth regulators (ZPTs), organic matter, and environmental conditions. However, using tissue culture raises various ethical considerations with synthetic ZPTs. This study aims to analyze the respondents' level of understanding of the application of bioethical aspects in the use of synthetic growth regulators in Granola potato tissue culture. L and determine their perceptions of the impact of the use of synthetic ZPT on the environment and the sustainability of production. This research was conducted for 22 days, starting on February 27, 2025 until March 21, 2025. The location of this research was in the Tissue Culture Laboratory at one of the private agricultural institutions in Medan city. This type of research is using descriptive method. The results of this study indicate that however some respondents realize the importance of bioethical principles, such as work safety, the laboratory towards bioethics still varies. The results of this study indicate that while some respondents are aware of the importance of bioethical principles, such as work safety, environmental sustainability, and regulation of the use of chemicals, the implementation still has some obstacles, especially in the aspects of socialization, training, and supervision. In addition, respondents' perceptions of the impact of synthetic ZPT use on the environment and production sustainability are still not fully aligned with the practices applied in the laboratory. Keywords: ZPT, Granola. L, Tissue Culture. Abstrak Kultur jaringan adalah teknik yang digunakan untuk memperbanyak tanaman melalui jaringan atau organ tanaman steril. Keberhasilan kultur jaringan kentang dipengaruhi oleh faktor seperti media kultur, zat pengatur tumbuh (ZPT), bahan organik, dan kondisi lingkungan. Penggunaan ZPT sintetis menimbulkan pertimbangan etis terkait dampaknya terhadap lingkungan dan keberlanjutan produksi. Penelitian ini bertujuan untuk menganalisis pemahaman responden terhadap penerapan aspek bioetika dalam penggunaan ZPT sintetis pada kultur jaringan kentang Granola L serta menilai persepsi mereka mengenai dampak lingkungan dan keberlanjutan produksi. Penelitian ini berlangsung selama 22 hari, dari 27 Februari hingga 21 Maret 2025, di Laboratorium Kultur Jaringan pada salah satu instansi pertanian swasta di Medan dengan metode deskriptif. Hasil penelitian menunjukkan bahwa sebagian responden menyadari pentingnya prinsip bioetika, seperti keselamatan kerja, keberlanjutan lingkungan, dan regulasi bahan kimia. Namun, penerapannya masih menghadapi kendala pada aspek sosialisasi, pelatihan, dan pengawasan. Selain itu, persepsi responden terhadap dampak ZPT sintetis terhadap lingkungan dan keberlanjutan produksi belum sepenuhnya sejalan dengan praktik yang diterapkan di laboratorium. Kata kunci: ZPT, Granola. L, Kultur Jaringan.